2023
DOI: 10.3389/fpls.2023.1093913
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of the PP2C gene family in peanut (Arachis hypogaea L.) and the identification of candidate genes involved in salinity-stress response

Abstract: Plant protein phosphatase 2C (PP2C) play important roles in response to salt stress by influencing metabolic processes, hormone levels, growth factors, etc. Members of the PP2C family have been identified in many plant species. However, they are rarely reported in peanut. In this study, 178 PP2C genes were identified in peanut, which were unevenly distributed across the 20 chromosomes, with segmental duplication in 78 gene pairs. AhPP2Cs could be divided into 10 clades (A-J) by phylogenetic analysis. AhPP2Cs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…PP2Cs represent more than 60% of the total phosphatase repertoire, with 80, 90, 91, and 88 genes identified in Arabidopsis , rice, tomato, and hot pepper genomes, respectively (Singh et al., 2016 ). Sequence and gene structure analyses of the PP2C family members in different plant species support their conservation in higher plants (Guo, Shi, et al., 2023 ; Wu et al., 2023 ). Similar to that observed in earlier studies (Ayatollahi et al., 2022 ; Couto et al., 2016 ; Sidonskaya et al., 2016 ), although mutant plants showed a more prominent response to immune signals, no autoimmunity was detected in pp2c5 and pp2c15 mutant plants (Figures 1 , 2 , 3 , 4 , 5 ).…”
Section: Discussionmentioning
confidence: 96%
“…PP2Cs represent more than 60% of the total phosphatase repertoire, with 80, 90, 91, and 88 genes identified in Arabidopsis , rice, tomato, and hot pepper genomes, respectively (Singh et al., 2016 ). Sequence and gene structure analyses of the PP2C family members in different plant species support their conservation in higher plants (Guo, Shi, et al., 2023 ; Wu et al., 2023 ). Similar to that observed in earlier studies (Ayatollahi et al., 2022 ; Couto et al., 2016 ; Sidonskaya et al., 2016 ), although mutant plants showed a more prominent response to immune signals, no autoimmunity was detected in pp2c5 and pp2c15 mutant plants (Figures 1 , 2 , 3 , 4 , 5 ).…”
Section: Discussionmentioning
confidence: 96%
“…In our study, two genes ( arahy.SJ8MZN and arahy.CRLU4M ) encode mitogen-activated protein kinase kinase kinase 3 (MAPKKK), which plays an essential role in MAPK signal perception, transduction, and amplification [ 38 ]. Additionally, phosphatase 2C 51 (encoded by arahy.8GI8KI ), a component of ABA signal transduction, is known to directly participate in plant salt stress regulation [ 59 , 60 ]. Furthermore, the hub gene arahy.ID0B6N encodes peroxidase 3, which plays a significant role in antioxidant responses and stress tolerance in plants, contributing to salt tolerance in soybean as well [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on motif distribution in Arabidopsis [ 10 ], rice [ 10 ], and cucumber [ 56 ] PP2C genes demonstrated that motifs were particular to only one or more subgroups which support our findings. Notably, the number of identified conserved motifs in HanPP2C (20 motifs) is higher than cucumber (10 motifs) [ 56 ], tomato (10 motifs) [ 31 ], peanut (10 motifs) [ 92 ], Arabidopsis (11 motifs) [ 10 ], and Medicago truncatula (15 motifs) [ 9 ].…”
Section: 0 Discussionmentioning
confidence: 99%
“…This study revealed that all 53 pairs of duplicated HanPP2c genes predominantly evolved through purifying selection. Previous investigation on tomato [ 31 ] and peanut [ 92 ] PP2C genes showed that all duplicated SIPP2C and AhPP2C genes have evolved from purifying selection. However, both purifying and positive selection were identified in the duplicated PP2C genes of woodland strawberries and pineapple strawberries [ 80 ].…”
Section: 0 Discussionmentioning
confidence: 99%